2011
DOI: 10.2166/wqrjc.2011.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature thermochemical pretreatment on sludge reduction potential of membrane bioreactor treating primary treated dairy wastewater

Abstract: In this present study, an aerobic submerged membrane bioreactor (MBR) was used to study the effect of thermochemical pretreatment on the efficiency of sludge reduction. For this purpose, two MBRs were fabricated. Between the two MBRs, one acted as a control reactor (CMBR) and the other acted as an experimental reactor (EMBR). The MBRs were operated with a mixed liquor suspended solids (MLSS) concentration in the range of 6,800-7,200 mg/L for a period of 160 days. In the EMBR, part of the MLSS was withdrawn at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…However, the inorganic fraction of the degraded cells did not accumulate in the EMBR and presumably permeated through the membrane as ionic species. Similar to our study, while working on integration of sludge disintegration system in A 2 O treating domestic wastewater, Banu et al [4] have reported, that there is no change in volatile fraction of the mixed liquor before and after the sludge pretreatment.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…However, the inorganic fraction of the degraded cells did not accumulate in the EMBR and presumably permeated through the membrane as ionic species. Similar to our study, while working on integration of sludge disintegration system in A 2 O treating domestic wastewater, Banu et al [4] have reported, that there is no change in volatile fraction of the mixed liquor before and after the sludge pretreatment.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, sludge reduction experiments were carried out at a fixed MLSS range of 7,000-7,200 mg/L. It was clear that the sludge reduction could be increased by operating the MBR at relatively high MLSS concentrations [4]. At high MLSS concentrations, the sludge yield was comparatively lower than at low MLSS concentrations, and the designed pretreatment Q also carried more solids for disintegration.…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations